Genomic Analysis of Clostridium perfringens Bacteriophage φ3626, Which Integrates into guaA and Possibly Affects Sporulation - Zimmer, Markus (American Society for Microbiology, 2002)
Two temperate viruses, φ3626 and φ8533, have been isolated from lysogenic Clostridium perfringens strains. Phage φ3626 was chosen for detailed analysis and was inspected by electron microscopy, protein profiling, and host range determination. For the first time, the nucleotide sequence of a bacteriophage infecting Clostridium species was determined. The virus belongs to the Siphoviridae family of the tailed phages, the order Caudovirales. Its genome consists of a linear double-stranded DNA molecule of 33,507 nucleotides, with invariable 3′-protruding cohesive ends of nine residues. Fifty open reading frames were identified, which are organized in three major life cycle-specific gene clusters. The genes required for lytic development show an opposite orientation and arrangement compared to the lysogeny control region. A function could be assigned to 19 gene products, based upon bioinformatic analyses, N-terminal amino acid sequencing, or experimental evidence. These include DNA-packaging proteins, structural components, a dual lysis system, a putative lysogeny switch, and proteins that are involved in replication, recombination, and modification of phage DNA. The presence of genes encoding a putative sigma factor related to sporulation-dependent sigma factors and a putative sporulation-dependent transcription regulator suggests a possible interaction of φ3626 with onset of sporulation in C. perfringens. We found that the φ3626 attachment site attP lies in a noncoding region immediately downstream of int. Integration of the viral genome occurs into the bacterial attachment site attB, which is located within the 3′ end of a guaA homologue. This essential housekeeping gene is functionally independent of the integration status, due to reconstitution of its terminal codons by phage sequence.